2005
DOI: 10.1021/bi047878d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mutation on the Regulatory Properties of Phospholamban in Co-Reconstituted Membranes

Abstract: Reconstitution into proteoliposomes is a powerful method for studying calcium transport in a chemically pure membrane environment. By use of this approach, we have studied the regulation of Ca(2+)-ATPase by phospholamban (PLB) as a function of calcium concentration and PLB mutation. Co-reconstitution of PLB and Ca(2+)-ATPase revealed the expected effects of PLB on the apparent calcium affinity of Ca(2+)-ATPase (K(Ca)) and unexpected effects of PLB on maximal activity (V(max)). Wild-type PLB, six loss-of-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
136
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(161 citation statements)
references
References 45 publications
(114 reference statements)
22
136
3
Order By: Relevance
“…We also confirmed that PLB molecules of normal inhibitory strength (N30C-PLB) do not significantly affect the V max of the Ca 2ϩ -ATPase (1). This is contrary to conclusions of several recent studies in which PLB was reported to either decrease (22) or increase (20,21,23) the V max of the Ca 2ϩ -ATPase. Using our viral constructs and the 2D12 antibody, Waggoner et al (22) recently noted a modest reduction (ϳ20%) in the V max of SERCA2a co-expressed with wild-type PLB compared with SERCA2a expressed alone.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that PLB molecules of normal inhibitory strength (N30C-PLB) do not significantly affect the V max of the Ca 2ϩ -ATPase (1). This is contrary to conclusions of several recent studies in which PLB was reported to either decrease (22) or increase (20,21,23) the V max of the Ca 2ϩ -ATPase. Using our viral constructs and the 2D12 antibody, Waggoner et al (22) recently noted a modest reduction (ϳ20%) in the V max of SERCA2a co-expressed with wild-type PLB compared with SERCA2a expressed alone.…”
Section: Discussioncontrasting
confidence: 99%
“…4B). The studies in which wild-type PLB and some other PLB mutants were reported to actually increase the V max of the Ca 2ϩ -ATPase were all conducted with the purified rabbit skeletal muscle enzyme co-reconstituted with purified PLB from detergent solution (20,21,23). In this case, it is possible that enzyme protection by PLB during the reconstitution process may have artifactually affected the results, as was recently suggested (23).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution versus Cardiac SR-The proteoliposomes used herein contain both SERCA1a and PLN oriented with their cytoplasmic domains on the external surface of the vesicles at lipid/protein ratios similar to those of cardiac SR membranes (19,29). Although there may be subtle differences in the interaction of PLN with SERCA1a versus SERCA2a (31), the skeletal muscle isoform is well established as a surrogate for structural and functional studies of the complex (for examples, see Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Mutants were confirmed by DNA sequencing (TAGC Sequencing, University of Alberta) and MALDI-TOF mass spectrometry (Institute for Biomolecular Design, University of Alberta). To phosphorylate PLN, purified PLN was solubilized in detergent and treated with the catalytic subunit of PKA (Sigma-Aldrich) (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation